Buoyancy and Stability Analysis of Ark’a Modulam Amphibious Foundation Model - Nomeritae Nomeritae; Wijanarka Wijanarka; Rudi Waluyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
To solve problems of settlement in floodplain areas, research on anti-flood foundation model is crucial. The anti-flood foundation model should be able to float during flood and to remain on land during non-flood conditions. This research focused on an amphibious foundation model named Ark’a Modulam. The reliability of Ark’a Modulam floating construction was analyzed for buoyancy and stability against vertical and horizontal loads. Two floating constructions were designed based on knock down and rigid systems. Both systems were designed using iron pipes with 2.5” and 4